(untitled) (Global Journal of Medical Research, 2022)
Diabetes mellitus DM is a chronic metabolic disorder characterized by persistent hyperglycemia It may be due to impaired insulin secretion resistance to peripheral actions of insulin or both According to the International Diabetes Federation